Climate and population: risk exposure to precipitation concentration in mainland Spain (1950-2010) - Roberto Serrano Notivoli; María Zúñiga-Antón; Ángel Pueyo; Santiago Beguería; Miguel Ángel Saz; Martín de Luis (Boletín de la Asociación de Geógrafos Españoles)
The term risk exposure combines the notions of natural hazard and the human exposure to that hazard. Spatial and temporal variations in risk exposure, therefore, can be caused by changes in hazard, in exposure, or both. In this work a novel methodology for computing and representing risk exposure and its temporal changes are presented, and applied to the analysis of risk exposure to extreme rainfall in mainland Spain between 1950 and 2010. For that, two complementary high-resolution gridded datasets, one of population potentials and another one of precipitation concentration, are combined. Despite a great spatial variability over time, the highest exposure was consistently found in the surrounding areas of the largest cities and along the Mediterranean coast. The relative influence of population changes and precipitation concentration evolution is analyzed. Results suggest that hazard (precipitation concentration) changes led most of the observed changes in risk exposure, except in those decades where population movements were massive and widespread.